2016
DOI: 10.20471/acc.2016.55.04.05
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cormack Lehane Grading System and Intubation Difficulty Score in Patients Intubated by D-Blade Video and Direct Macintosh Laryngoscope: A Randomized Controlled Study

Abstract: SUMMARY -D-blade is a relatively new device in the fi eld of videolaryngoscopy, designed for airway management by enabling indirectoscopic glottic view. In our study, we investigated effi ciency of D-blade in comparison with direct Macintosh laryngoscope (gold standard). Fifty-two adult patients with normal airway scheduled for elective surgery in general anesthesia were randomly assigned in D-blade video or direct Macintosh group. In the fi rst video group, patients were laryngoscoped and intubated by D-blade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…The characteristics of the included studies are shown in Table 1 [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ,…”
Section: Resultsunclassified
See 2 more Smart Citations
“…The characteristics of the included studies are shown in Table 1 [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ,…”
Section: Resultsunclassified
“…In the rank analysis using SUCRA, CMD was the overall most successful VL (SUCRA 77.7) and in the context of difficult airway (SUCRA 85.2) status. The pooled success rates of CMD were 90.6% (358/395 patients) in the all airway status category (the range of success rate = 81–100% in eight included studies) [ 13 , 29 , 61 , 78 , 89 , 92 , 93 , 103 ] and 92.7% (178/192 patients) in the difficult airway status category (the range of success rate = 92–95% in three included studies) [ 29 , 61 , 89 ]. In the normal airway status category, King Vision was the most successful (SUCRA 72.7), and the pooled success rate of King Vision was 92% (169/183 patients; the range of success rate = 68–100% in five included studies) [ 30 , 47 , 48 , 78 , 88 ] ( Figure 3 , Figure 4 and Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation